Development and validation of a scale for assessing personal digital content management skills of higher education students - Kocak, Omer (Malaysian Journal of Library and Information Science, 2021)
The management of high quantities and large volumes of digital content has become one of the most important skills today. Information or content that cannot be managed well can be considered as unnecessary or garbage in this period of intensive digitalization. In this study, a scale was developed to determine personal digital content management skills, which are important skills for higher education in the 21st century. The sample of this study consists of 600 students from different degree levels, departments and universities in Turkey. Personal Digital Content Management Scale (PDCMS) is a five-point Likert-type scale, consisting of 38 items operationalised under seven main skill dimensions - organizing, erasing, digital literacy, privacy, search-retrieval, management of course documents, and backup. The validity and reliability of the scale have been determined by conducting exploratory factor analysis, confirmatory factor analysis, item distinctiveness analyses, and evaluating internal consistency coefficients. As a result, a valid and reliable measurement tool to be used to measure the personal content management skills of the students in higher education has been developed. In this context, it could be said that PDCMS could make significant contributions to the digital skills literature., especially on instruments used to measure digital content management skills.